2021
DOI: 10.3390/antibiotics10010041
|View full text |Cite
|
Sign up to set email alerts
|

A New Promising Anti-Infective Agent Inhibits Biofilm Growth by Targeting Simultaneously a Conserved RNA Function That Controls Multiple Genes

Abstract: Combating single and multi-drug-resistant infections in the form of biofilms is an immediate challenge. The challenge is to discover innovative targets and develop novel chemistries that combat biofilms and drug-resistant organisms, and thwart emergence of future resistant strains. An ideal novel target would control multiple genes, and can be inhibited by a single compound. We previously demonstrated success against Staphylococcus aureus biofilms by targeting the tRNA-dependent regulated T-box genes, not pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…More specifically, analog PKZ18-22 exhibited a significant effect on the expression of eight out of 12 T-box regulated genes on MRSA and did not affect the 5′ UTR of other genes, as revealed by RNA sequencing. It was found that PKZ18-22 has a wider range of biofilm-inhibiting properties and is 10 times more effective than frequently used antibiotics such as vancomycin [ 72 ]. Additionally, the very low levels of resistance to PKZ18 analogs supports the specific binding of them on different T-boxes and represents attractive small-molecule antibacterial drugs for future research and clinical use due to their diversified T-box targets, their minimal occurrences of resistance and their synergy with other antibiotics [ 71 ].…”
Section: T-box Riboswitchesmentioning
confidence: 99%
“…More specifically, analog PKZ18-22 exhibited a significant effect on the expression of eight out of 12 T-box regulated genes on MRSA and did not affect the 5′ UTR of other genes, as revealed by RNA sequencing. It was found that PKZ18-22 has a wider range of biofilm-inhibiting properties and is 10 times more effective than frequently used antibiotics such as vancomycin [ 72 ]. Additionally, the very low levels of resistance to PKZ18 analogs supports the specific binding of them on different T-boxes and represents attractive small-molecule antibacterial drugs for future research and clinical use due to their diversified T-box targets, their minimal occurrences of resistance and their synergy with other antibiotics [ 71 ].…”
Section: T-box Riboswitchesmentioning
confidence: 99%
“…Third, there are number of novel antimicrobial materials that should be investigated for their suitability to be formulated into a suitable form to be used as additives for an AFAMBC. Examples of materials that could be added to the powder of a plain cement are a quorum-sensing inhibitor drug[ 113 ], Ti-doped ZnO[ 114 ], nano-GO nanosheets[ 115 ], selenium nanoparticles[ 116 ], Ag-nanoparticle-reduced GO nanocomposite[ 117 ], chitosan hybrid nanoparticles[ 118 ], a Cu cluster molecule[ 119 ], powder prepared from extract from a Tunisian lichen[ 120 ], Yb-doped ZnO nanoparticles[ 121 ], and an analog of PKZ18 (PKZ18-22), a molecule that has been shown to block growth of antibiotic-resistant S. aureus in biofilm[ 122 ]. Examples of materials that could be added to the liquid of a plain cement are benzothiazole or one of its derivatives[ 123 , 124 ] and a natural antimicrobial agent (such as extract of Salvadora persica , Olea europaea , and Ficus carcia leaves[ 125 ] or biosynthesized ZnO nanoflowers[ 126 ]).…”
Section: Future Prospectsmentioning
confidence: 99%
“…In addition to the advantages of directly disintegrating biofilms, it may also directly shadow the dormant cells or newly dividing cells, leading to unique therapeutic effects [ 232 ]. Thorsten M. Seyler et al reported a derivative of PKZ18 (PKZ18-22) for the first time, which can selectively target Gram-positive bacteria [ 233 ]. CRISPR interference (CRISPRi) was also one of the main technologies developed in the field of anti-infection [ 234 ].…”
Section: Strategies Of Targeting Initial Adhesion Stagementioning
confidence: 99%